Pengaruh Penerapan Green Accounting dan Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan Pertambangan yang Tercatat di Bursa Efek Indonesia Periode Tahun 2020-2022 - Regina Siri; Eko Cahyo Mayndarto; Shofia Asry (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine 1) the effect of implementing green accounting on the company's financial performance, 2) the effect of corporate social responsibility on the company's financial performance, and 3) the effect of implementing green accounting and corporate social responsibility on the financial performance of mining companies listed on the Indonesia Stock Exchange in 2020-2022. The method in this study uses a quantitative method. The data sources used in this study are secondary data types and the sampling technique uses the purposive sampling method by obtaining 10 companies out of 63 companies with a total of 30 annual reports listed on the Indonesia Stock Exchange in 2020-2022 which will be the object. Data analysis used in this study is descriptive statistical analysis, classical assumption tests, and simple regression tests. The results of this study indicate that the implementation of green accounting has a positive and significant effect on the company's financial performance, corporate social responsibility has a positive and significant effect on the company's financial performance and the implementation of green accounting and corporate social responsibility also simultaneously has a positive and significant effect on the company's financial performance